Seraphina - Hartman, Rachel 1972- (Ember, 2013)
Four decades of peace have done little to ease the mistrust between humans and dragons in the kingdom of Goredd. Seraphina Dombegh has reason to fear both sides. An unusually gifted musician, she joins the court just as a member of the royal family is murderedNin suspiciously draconian fashion.